1999
DOI: 10.1037/0096-1523.25.5.1284
|View full text |Cite
|
Sign up to set email alerts
|

Postural coordination modes considered as emergent phenomena.

Abstract: The coordination of multiple body segments (torso and legs) in the control of standing posture during a suprapostural task was studied. The analysis was motivated by dynamical theories of motor coordination. In 2 experiments it was found that multisegment postural coordination could be described by the relative phase of rotations around the hip and ankle joints. The effective length of the feet, the height of the center of mass, and the amplitude of head motions in a visual tracking task were varied. Across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
167
3
15

Year Published

2001
2001
2007
2007

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(212 citation statements)
references
References 81 publications
(174 reference statements)
27
167
3
15
Order By: Relevance
“…Studies involving standing and visual tracking [22; 144; 239], as well as steady-state standing in the context of gravity (so-called 'quiet standing') [60], have shown that the human body spontaneously adopts two co-existing modes of movement during upright standing, rather than a continuum of mixed strategies [60]. These consist of an in-phase mode, with the ankle-hip joints moving simultaneously in the same direction, and an antiphase mode, with the two joints oscillating simultaneously in opposite directions, one-mode predominating depending on sensory, environmental and intentional (emotional-cognitive) conditions [22].…”
Section: Posture Controlmentioning
confidence: 99%
“…Studies involving standing and visual tracking [22; 144; 239], as well as steady-state standing in the context of gravity (so-called 'quiet standing') [60], have shown that the human body spontaneously adopts two co-existing modes of movement during upright standing, rather than a continuum of mixed strategies [60]. These consist of an in-phase mode, with the ankle-hip joints moving simultaneously in the same direction, and an antiphase mode, with the two joints oscillating simultaneously in opposite directions, one-mode predominating depending on sensory, environmental and intentional (emotional-cognitive) conditions [22].…”
Section: Posture Controlmentioning
confidence: 99%
“…We cannot agree more and, as Myin notes, we made several references to this in the target article. Our own research has emphasized the task or goal-dependent nature of perception and action (e.g., Bardy et al 1999;Marin et al 1999;. However, the pickup of information is posterior to the existence of information.…”
Section: R4 Constraints On Specificationmentioning
confidence: 99%
“…[52][53][54] On the other hand, examples of behavioral approaches to assess postural dynamics have included the following assessments: postural sway and gross movements via video photographic analysis, electromagnetic tracking devices to monitor 3-dimensional position and orientation (continuous measurements) of small sensors attached to anatomic structures with respect to a transmitter, 48 and optoelectronic recording. 44 The medical profession has not typically managed posture well. However, physical therapy such as the McKenzie method, 55,56 osteopathy, 57 and chiropractors such as with the chiropractic biophysics (CBP) technique 22 have all addressed management issues of postural correction.…”
Section: Postural Alignment and Chiropractic Subluxationmentioning
confidence: 99%
“…Including these regions, it is now possible to depict both the biomechanical and behavioral constraints for a given posture. For a detailed account of how postural control is influenced by biomechanical and behavioral constraints (and data-based depictions of the tolerance and reversibility regions), see Bardy et al, 44 who studied how alterations of these factors affect postural coordination.…”
Section: Posture From a Behavioral Perspectivementioning
confidence: 99%